Pengembangan Kompetensi Guru PAI Dalam Pembelajaran Berbasis Teknologi Untuk Mendorong Moderasi Beragama Di Era Digital - Hestiarini Utami, Tika; Listiana, Heni; Jannah, Faridatul; Badriyah, Khoirina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2024)
This research discusses developing the competency of Islamic Religious Education (PAI) teachers in technology-based learning to encourage religious moderation in digital era. The competence of qualified teachers is very necessary considering that technological development have brought major changes to learning methods including PAI to be able to meets the demands of the times. This research methods is library research where researchers collect data from various existing literature and then analyze and describe it to make it easier to understand. The results of this research reveal that education is a means of instilling thhe value of religious moderation from early age. The urgency for developing PAI’s teacher competency is to be able to provide affective and efficient learning. Then the role technology it self in strengthening religious moderation in PAI learning is as a means of delivering material, as a means of voicing religious moderation, and developing attitudes of tolerance and moderation.